The genesis and development of ideological and theoretical aspects of the formation of the concepts of the “third way” in the East - Sergey A. Voronin (RUDN Journal of World History)
The significance of this topic is determined by the crisis of the Western model of “consumer society” and the demand for finding new, different ways of development from previous socio-economic systems. One of which is the “third way” in the countries of the East. Attention is focused on the revival and revival in recent years of the “non-aligned movement” that arose in the late 50s and early 60s of the last century. The leaders of this movement also became the authors of original political and legal doctrines of social development along the “third way”. The research reveals the difference between the concepts of development along the “third way” in the West and in the East. The author pays special attention to the fact that the leaders of the countries of the East, the architects of development concepts along the “third way”, were looking for their own authentic path of development, rejecting the capitalism of Adam Smith and the communism of Karl Marx, that is, refusing to follow both the capitalist and socialist paths of development of minority power over the majority. The purpose of the study is to identify the theoretical sources of the formation of the concepts of the “third way”, to clarify the basic principles underlying the theories of the “third way”, and to carry out their typologization. The study also reveals the relationship and continuity between the ideological principles of the anti-colonial and national liberation movement of the 19th century and the doctrines of the “third way” of the 20th century. The methodological basis of the study is the principles of historicism, scientific objectivity, and a critical attitude to the source base. The main results of the study can be in demand and used within the framework of research activities, during lectures and seminars on the modern and contemporary history of Asian and African countries.